2020
DOI: 10.1109/access.2020.2999106
|View full text |Cite
|
Sign up to set email alerts
|

Research on Music Visualization Based on Graphic Images and Mathematical Statistics

Abstract: Music visualization can present music information through the visual way of graphic images, which is helpful to improve the accuracy and effectiveness of music information communication. In view of the shortcomings in the current music visualization field, this paper combines K-means clustering, fusion decision tree and other mathematical statistical methods on the basis of music graphic images to construct a music visualization model based on graphic images and mathematical statistics. First, the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…At present, the existing image enhancement technologies are mainly based on spatial domain and transform domain [8]. e former directly calculates the image gray level, and the main methods include direct gray level transformation, spatial filtering, and histogram processing [9].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the existing image enhancement technologies are mainly based on spatial domain and transform domain [8]. e former directly calculates the image gray level, and the main methods include direct gray level transformation, spatial filtering, and histogram processing [9].…”
Section: Introductionmentioning
confidence: 99%
“…• Music dynamics: Real-time animation generates based on the music data when it is playing. At the same time, the mapping elements are consistent with the feeling and emotion of the audiences [12] .…”
Section: Visual Elements Mappingmentioning
confidence: 54%
“…Besides, [30] found that using personalized visualizations helped students with different learning styles to understand chemistry concepts better. With the increasing use of artificial intelligence in education, there is potential for visualizations to be integrated with AI technologies to provide personalized learning experiences [31]. For example, visualizations could be used to help AI systems understand a student's learning style and adjust their approach accordingly.…”
Section: The Future Direction Of the Graphic Visualization Approach I...mentioning
confidence: 99%